Rogue : a novel - Miller-Lachmann, Lyn, 1956- (New York, NY : Nancy Paulsen Books, 2013)
An eighth-grade girl with Asperger's syndrome tries to befriend her new neighbor, facing many challenges along the way.
Keywords: Asperger's syndrome -- Juvenile fiction; Autism -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Friendship -- Juvenile fiction; Multiracial people -- Juvenile fiction